(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The current study was carried out to screen and assess the antibacterial activity of Jatropha curcas ethanol leaf extracts against some bacteria isolated from oral cavity of some students of Federal University Dutsin-Ma (FUDMA), Katsina State, Nigeria. A fresh leaf of the plant was collected, air dried, homogenized and extracted using 95% Ethanol. A total of twenty (20) oral cavity samples were collected using sterile swab sticks and process using microbiological standard techniques, the bacterial species was isolated using blood agar and confirmed using Gram’s staining and biochemical tests. A preliminary phytochemical screening was performed using standard techniques. The existence of the phytochemical components of the J. curcas leaf ethanol extract was confirmed using (FTIR and GCMS). The ethanol leaf extract of J. cactus was tested for antibacterial activity using the agar well diffusion method. Phytochemical analysis gave positive results for alkaloids, Cardiac glycosides, Saponins, Tannins and Terpenoids. Octadecanoic acid 2,3-dihydroxypropyl ester (C21H42O4) was found as prominent phytoconstituent in the extract which probably contributed to the antibacterial effect of the J. curcas leaf extract. Streptococcus Species and S. aureus was isolated from oral cavity as common pathogens. J. curcas leaf extract showed promising with an inhibitory zone of (20mm) at 25 mg/ml for Streptococcus species and (18mm) at 25 mg/ml for Staphylococcus aureus, respectively. In conclusion J. curcas ethanol leaf extract could be a good candidate for antibacterial agent development against both gram positive and negative strains of.bacterial.